EFL Teacher Identity Development during Teacher Professional Education Programme - Suarcaya, Putu; Barustyawati, Anak Agung Sri; Syafryadin (Universitas Cokroaminoto Palopo, 2023)
This study aims to identify the development of teacher participants of PPG. The development of the identity is considered urgent to explore especially because PPG is conducted fully online facilitated by an LMS. Instructors and participants are required to conference online and do assignments online as well as teaching practice. The current stud is conducted based on content analysis method involving six respondents. Data was interpreted from recordings during online discussion session.The research findings indicate that the new skills acquired during PPG fall within the area of use of technology, pedagogy, and collaboration.